The Charlson comorbidity index as a predictor of outcomes in liver transplantation: single-center experience. (2012)
Several comorbidity indices, such as the Child-Turcotte-Pugh (CTP) score and the Model for End-Stage Liver Disease (MELD) score, have been used to optimize available organ resources and adjust priorities in diagnosis and allocation of grafts for patients who are candidates for liver transplantation. There have also been various attempts to create instruments to accurately predict outcomes after liver transplantation, but none has proved to be truly applicable, with the exception of the Charlson comorbidity index (CCI). We retrospectively reviewed data of 221 liver recipients, including living-related liver transplantation and multiple organ transplantation performed between January 2006 and September 2009. Survival analysis revealed a significant association of the CCI with decreased posttransplantation patient survival (P = .003). Furthermore, Kaplan-Meier plots and log-rank test showed a significant association between graft survival and the score (P = .039). Our data suggest that the CCI is a simple tool for the evaluation of comorbidity and that increased preoperative patient comorbidity increases the risk of graft loss and patient death after liver transplantation. The CCI should be considered an important tool for improving patient care because of its potential applications for patient management.